Analisis Kausalitas Infrastruktur Fisik, Infrastruktur Sosial dengan Pertumbuhan Ekonomi di ASEAN Tahun 2008-2017 - Diki Prasetyo; Gadi Sasana (Universitas Diponegoro, 2020)
This study aims to determine the causality relationship between physical infrastructure and social infrastructure variables with economic growth. This study uses secondary data in the form of panel data in 10 ASEAN countries from 2008-2017. Data analysis tools used in this study are the Granger Causality Test and the Panel Vector Error Correction Model (P-VECM). Based on the Granger Causality Test, there is a bidirectional causality relationship between the electric power consumption and the economic growth and there is also a bidirectional causality relationship between the health expenditure per capita and the economic growth, addition there is a one-way relationship (unidirectional) between the air transportation, cargo and the economic growth. Based on the Panel Vector Error Correction Model (P-VECM) test there is a long- term relationship between the fixed telephone subscriptions to the economic growth with negative and significant effects, then there is a long-term relationship between the government expenditure for education to the economic growth with a positive and significant effect, then there is a long-term relationship between the health expenditure per capita to the economic growth with a positive and significant effect and there is a long-term relationship between the health expenditure % of GDP to the economic growth with a positive and significant influence.